BidSi6 and BidEL isoforms as a potential marker for predicting colorectal adenomatous polyps - Flora Forouzesh; Fatemeh Sadat Kia; Ehsan Nazemalhosseini-Mojarad (BMC, 2022)
Abstract Background As a well-known protein, Bid links the extrinsic and intrinsic apoptotic pathways and plays important roles in cell proliferation. In this study, we evaluated the expression of two isoforms of the Bid gene (BidSi6 and BidEL) in colorectal adenomatous polyps as a biomarker and investigated the relationship between their expression levels with clinicopathological factors. Methods The expression of BidSi6 and BidEL isoforms in 22 pairs of Adenomatous polyps and adjust non-polyp tissues was measured by qReal-Time PCR and compared with 10 normal colon tissues. ROC curve was performed to examine the diagnostic capacity. Also, sequencing was performed for molecular identification of BidSi6 isoform in adenomatous polyp. Results Our results showed that BidSi6 and BidEL isoforms were significantly overexpressed in Adenomatous polyps and non-polyp adjacent tissues from the same patients compared to that in normal colon tissues, but there was no significant expression between polyps and adjust non-polyp tissues. There were no significant correlations between the expression of two isoforms and other features of clinicopathology. The area under the curve of BidSi6 and BidEL isoforms indicated powerful diagnostic capability. The phylogenetic tree was constructed based on the sequence of idSi6 isoform, and the results showed that adenomatous polyp tissue and adjust non-polyp tissue were separated from healthy colorectal tissue and reference sequence (EU678292). Conclusions These findings suggest that BidSi6 and BidEL isoforms can be used as new potential biomarkers in adenomatous polyps.